(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article explores the sustainable development of the green economy with a particular focus on the integration of ecological innovations and digital technologies. It highlights the importance of the green economy in ensuring ecological sustainability and mitigating environmental challenges while emphasizing the positive impacts of innovative technologies and digital transformation on the environment. The study analyzes strategies for enhancing economic efficiency through ecological innovations and digital solutions, discusses advanced international practices, and examines strategic approaches to sustainable development. The findings demonstrate that the integration of digital tools and eco-innovations is essential for achieving long-term environmental resilience and economic growth.